Aircraft Manufacturers Liability under the 1999 Montreal Convention (Case Study of Class Action against Boeing Company) - Fauzi, Valesca Vella Valdema; Danial, Danial; Sitamala, Afandi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
The Lion Air JT-610 plane crash on October 29 2018 killed all passengers and caused significant losses, both material and immaterial. This tragedy raises questions about the legal responsibility of Boeing, the aircraft manufacturer, particularly from an international law perspective. This study aims to analyze the possibility of Boeing's liability under the 1999 Montreal Convention, which serves as the primary instrument in regulating the liability of air carriers toward passengers and cargo. This study employs a normative legal method with a descriptive-analytical approach, using legal liability theory and justice theory as the basis for analysis. The results of the study show that the 1999 Montreal Convention only regulates liability between airlines (air carriers) and passengers, not between passengers and third parties such as aircraft manufacturers. In this context, Lion Air is responsible for providing initial compensation of 113,100 Special Drawing Rights (SDR) to the heirs of each passenger. However, under Article 37 of the Convention, Lion Air may seek liability from third parties, including Boeing, if it is proven that there were manufacturing defects or negligence contributing to the accident. Thus, although Boeing does not have direct liability toward passengers, indirect liability may arise through recourse by the airline. This opens an international legal avenue against manufacturers in cases of aviation accidents